Integrating Generative AI to in National Education System : Framework Work For Implementation Ethics in Developing Countries - Solikhah, Mar'atus; Komarudin, Komarudin (Journal of Artificial Intelligence Research, 2025)
Development Generative Artificial Intelligence (Generative AI) has rapidly open opportunity transformation in system education , especially in developing countries . However , integration technology This present challenge ethical , gap infrastructure and inequality digital literacy . Research This aim For formulate framework Work ethical use implementing Generative AI inclusive and responsible answer in system education national . Method research used​ is studies qualitative with multi- case approach in Indonesia, Kenya, and Bangladesh. Data collected through interview deep with stakeholders interest education , analysis document policies , as well as observation on the project pilot AI integration in schools . Research results show that success Generative AI integration is very depends on three main pillars : (1) clarity policy ethics AI usage , (2) readiness digital infrastructure and training educators , as well as (3) data protection and rights students . Framework proposed work​ covers guide practical based principle justice , transparency , and inclusiveness . Study This expected can become reference for developing countries in build ecosystem adaptive education​ to technology without sacrifice values ethics and justice social .